A Method to Provoke Obsessive Compulsive Symptoms for Basic Research and Clinical Interventions - Tendler, Aron; Sisko, Elyssa; Barnea-Ygael, Noam; Zangen, Abraham; Storch, Eric A. (Frontiers in Psychiatry, 2019)
The efficacy of deep repetitive transcranial magnetic stimulation (dTMS) for obsessive compulsive disorder (OCD) was recently confirmed in an FDA-regulated, multicenter, sham-controlled study. In this study, patients who failed pharmacotherapy underwent individually tailored provocations just prior to each stimulation session, in the attempt to activate the relevant circuitry and making it labile to change. The procedure that was developed reliably evoked moderate intensity symptoms, making it effective on the one hand and mild enough to allow the patient to continue with the dTMS session on the other. This methodology article describes in a detailed step wise fashion how to evaluate the patient’s specific symptoms and design the individualized provocations. Additionally, the article explains how to instruct relevant personnel to administer the provocations, gauge their efficacy, and overcome possible obstacles. This method, apart from its ongoing role in the clinical treatment of OCD by dTMS, may be used for provocation of symptoms in basic studies (e.g., imaging with EEG or fMRI) as well as other treatments.